Peningkatan hasil belajar bahasa indonesia materi menemukan ide pokok paragraf melalui model circ (Cooperative Integrated Reading and Composition) Pada siswa kelas V-C MIN 10 Aceh Besar - Zuhairawati, Zuhairawati (Jurnal Pendidikan dan Pengabdian Vokasi (JP2V), 2020)
This study aims to improve the ability to find the main ideas of paragraphs in class V-C students. This research is a Classroom Action Research (CAR) carried out through 2 cycles with stages of planning, implementation, observation, reflection. Based on the results of observations in the field the ability of students to find the main idea of the paragraph is still low. Most teachers do not use a fun learning mod-el. The situation has the potential to cause boredom and reduce student interest in learning. Based on the description above through this research is expected to improve student learning outcomes and increase teacher creativity in teaching. This study uses the CIRC (Cooperative Integrated Reading and Composi-tion) learning model. This research was carried out in MIN 10 Aceh Besar in class V-C students with a total of 25 students consisting of 14 male students and 11 female students. Based on the results of re-search conducted using the CIRC learning model an increase in student activity and learning outcomes in finding the main ideas of the paragraphs during the learning process takes place starting from cycle I to cycle II. This is proven, in the first cycle there are still many students who still feel confused in find-ing the main idea of the paragraph obtained in the first cycle 16 students (64.00%) are complete and 9 students (36.00%) have not finished with an average value of 70.80. Cycle II increased to 20 (80.00%) students who completed and those who did not complete 5 (20.00%) students with an average score of 81.20. From the implementation of the PTK cycle 1 and cycle II it can be concluded that learning by using the CIRC model can improve student learning outcomes and activities in Indonesian subjects in V-C MIN 10 Aceh Besar class students.